Sistem Pendaftaran Siswa Baru Di SMP 8 Bengkulu Menggunakan Metode Multilevel Queue - Dede Maulana Ibrahim; Apridiansyah, Yovi; AR Wallad Mahfuzi; Pahrizal (LPPMPP Yayasan Sejahtera Bersama Bengkulu, 2024)
New student registration is the initial stage process for new students to be able to carry out education in the school environment. An efficient and effective registration process is important for every school to ensure that every prospective student gets a fair and equal opportunity to get a quality education. SMP Negeri 8 Bengkulu also admits new students, but in this case SMP 8 Bengkulu registration is still done manually which results in frequent data errors. Another problem that is often faced is the complexity of the registration process which takes time so that the registration process is slow because this registration process involves collecting personal information, documents, filling out forms, selecting classes, and meeting various other requirements. This process not only requires the involvement of prospective students and parents, but also involves school officials in managing and verifying data. The solution to this problem is to create an online registration system for new students at SMPN 8 Bengkulu. The registration system can be completed by using the Multilevel Queue method which is one of the methods in overcoming the queue problem. This method can group small queues where each queue will run with the FCFS (First Come First Serve) method. In the context of the new student registration system, the Multilevel Queue method can be used to set priorities and schedule the processing of registration data, thus ensuring the smooth process of registering new students efficiently and accurately. This system can also help the process of registering new students at SMPN 8 Bengkulu City.